WASTES WILL CUT OUT MDF AS RAW MATERIAL FOR PRODUCTION OF LINEAR ELEMENTS - Koval, Lyubomyr (Forestry, Forest, Paper and Woodworking Industry, 2024)
An amount of import and export of MDF in Ukraine and some countries of Europe is given in the article. Classification of wastes which appear during a process of cutting out MDF is developed and given. Typical maps about cutting out MDF for the production of doors are analysed. On the basis of this analysis is given dependence between using of cutting tailings and the width of type. On the basis of classification of well-educated wastes and analysis of technological processes the chart of technological process of production of linear elements is developed from cutting out MDF wastes.